GMMA and Glycoconjugate Approaches Compared in Mice for the Development of a Vaccine against Shigella flexneri Serotype 6 - Maria Michelina Raso; Gianmarco Gasperini; Renzo Alfini; Fabiola Schiavo; Maria Grazia Aruta; Martina Carducci; Maria Concetta Forgione; Silvia Martini; Paola Cescutti; Francesca Necchi; Francesca Micoli (Vaccines, 2020)
Shigella infections are one of the top causes of diarrhea throughout the world, with Shigella flexneri being predominant in developing countries. Currently, no vaccines are widely available and increasing levels of multidrug-resistance make Shigella a high priority for vaccine development. The serotype-specific O-antigen moiety of Shigella lipopolysaccharide has been recognized as a key target for protective immunity, and many O-antigen based candidate vaccines are in development. Recently, the Generalized Modules for Membrane Antigens (GMMA) technology has been proposed as an alternative approach to traditional glycoconjugate vaccines for O-antigen delivery. Here, these two technologies are compared for a vaccine against S. flexneri serotype 6. Genetic strategies for GMMA production, conjugation approaches for linkage of the O-antigen to CRM197 carrier protein, and a large panel of analytical methods for full vaccine characterization have been put in place. In a head-to-head immunogenicity study in mice, GMMA induced higher anti-O-antigen IgG than glycoconjugate administered without Alhydrogel. When formulated on Alhydrogel, GMMA and glycoconjugate elicited similar levels of persistent anti-O-antigen IgG with bactericidal activity. Glycoconjugates are a well-established bacterial vaccine approach, but can be costly, particularly when multicomponent preparations are required. With similar immunogenicity and a simpler manufacturing process, GMMA are a promising strategy for the development of a vaccine against Shigella.